Serum Ferritin and Gestational Diabetes Mellitus: A Case Controlled Study - Islam, Nilufar; Chowdhury, Shiuly; Kazal, Rezaul Karim; Rahman, Reefat; Parveen, Hasna Hena; Farhana, Kazi; Chowdhury, Saleha Begum (Journal of Bangladesh College of Physicians and Surgeons, 2013)
J Bangladesh Coll Phys Surg 2012; 30: 205-210 DOI: http://dx.doi.org/10.3329/jbcps.v30i4.14763